A study on online and offline shopping in malaysia - Noratikah, Abu; Nureen Naileen, Mohamad Ramdzan (2022)
Online shopping is an online purchase for shoppers to save their time without leaving home while offline shopping is a traditional method of shopping in which customers physically visit a store buying their needs. Number of online shopping platforms has increasing due to the country’s development and the increase of places where people can access the internet and given the opportunity for them to shop anywhere. The offline shopping costs the customer’s time and effort, but also provides enjoyment because they can evaluate the products, they wished to buy by themselves. The propose of this study is to analyse the satisfaction and preference of customers for online and offline shopping in Malaysia. The data in this study will be collected using questionnaires and descriptive approach will be used to analyse the data. Results found that people satisfaction towards offline shopping is more than online shopping with the percentage of very satisfied 66.7% for offline and 18.5% for online. Besides that, people prefer online shopping compared to offline shopping with 17.6% differences.